Condiciones Laborales de los empleados del departamento de Servicio de Integración Laboral Fenedif Babahoyo - Bravo León, Mariuxi Aracelly (2019)
This case study is about the working conditions offered by the company FENEDIF to employees of the Department of Labor Integration Service in the city of Babahoyo, framed in the sub-line Administrative Management Model, for this investigation the modality methodology was used Qualitative Exploratory - Descriptive, with an inductive - deductive method that helped meet the objective which was to identify the working conditions of the employees of the Sil, the same that according to the interview made to the employees could be fully fulfilled , where it was determined that one of the conditions that most affects is the location and lack of a larger infrastructure to reduce the discomforts to which employees are exposed